MANAJEMEN PESANTREN DALAM MENUMBUHKAN KESADARAN BERAGAMA MAHASISWA: Studi di Pesantren Mahasiswa Al Manar Universitas Muhammadiyah Ponorogo - ABIDIN, ZAINAL (Universitas Islam Negeri Raden Intan Lampung, 2016)
This study discusses the management pesantren in growing religious awareness of students. A study at the seminary student of Al Manar Muhammadiyah University of Ponorogo. Pesantren students as offer solutions integration of science science and religion, and culture, as well as balancing the intellectual, emotional and spiritual. The findings of the study include: 1). Aspects of the management namely: a). Planning student Pesantren Al Manar include: determination vision, mission, aim, target, daily activity schedule, and activity sunday, Material:core and supplementary materia, results indicators learning; b) while pesantren management implementation leading the growth of religious consciousness of students namely: chant al matsurat, Quran recitations, Fard prayers in congregation, sunnah prayers rawatib, prayers tahajjud, sunnah fasting on Mondays and Thursdays, rote short letters juz 'amma. This is done by strategy Musyrif a good example and disciplinary time. c). Use evaluation: (1) Evaluation forms daily worship (2) Provide appropriate sanctions for those who break the rules, (3). Make the rules clear and fair for Musrif and students which is conducted by Mudabbir. (4). Provides strict sanctions for noncompliance both Musyrif and students. 2). While forms of religious awareness of students after attending a boarding school program are as follows: More diligent in praying, can carry out the sunnah fasting, can add rote short letters, and prayerprayer, can add an Islamic outlook and history of Islam, more often obligatory prayers with the congregation in the mosque, felt prayer tahajud with istiqomah, More often reading the Quran, comes the responsibility to carry out obligations. Keywords: management boarding school, students, religious awareness